Determinan Keberhasilan Turnaround pada Perusahaan yang Mengalami Financial Distress - Rizki Dwi Lestari; Ni Nyoman Alit Triani (BISMA (Bisnis dan Manajemen), 2018)
This study aims to determine the factor that influence the succes of the turnaround firm experiencing financial disstres. These factor are profitability ratio, severity, free assets, size, downsizing, and CEO turnover. The sample used in this study is a non-financial companies listed on IDX 2008-2012 period, which had financial disstres in 2008-2009 as many as 60 companies. Financial disstres companys was measured using the Altman Z-score. The data analysis technique used logistic regression. The research results indicate the accuracy level is 76,7%. Partially profitability ratio and size influence on success of the turnaround. Severity, free assets, downsizing, and CEO turnover does not influence on the success of the turnaround. While simultaneously profitability ratio, severity, free assets, size, downsizing, and CEO turnover influence on the success of the companys turnaround.